Pencegahan Intoleransi dan Radikalisme melalui Kurikulum Satuan Pendidikan: Studi Dokumen Kurikulum Pendidikan Hayuning Pakarti SMA Negeri 5 Yogyakarta - Darraz, Muhammad Abdullah (Universitas Muhammadiyah Prof Dr Hamka, 2024)
The education sector is recognised as an important and vital medium in preventing the infiltration of radicalism-extremism among the young generation. It is through education that young people can improve their cognitive-affective capacity through the cultivation of positive values, such as discipline, tolerance and critical thinking. Awareness efforts about the dangers of intolerance, radicalism, extremism and even acts of terrorism can be instilled through the education process, so that these negative things can be prevented as early as possible. This research aims to examine the role of education, especially school communities, in preventing radicalism-extremism among young students. This research will focus on the role that has been carried out in several school communities through the preparation of the School Operational Curriculum (KOSP) in efforts to prevent radicalism-extremism in school communities. This research uses a qualitative approach, by conducting a document studies related to the School Operational Curriculum prepared by SMA Negeri 5 Yogyakarta.